PENGARUH CURRENT RATIO(CR) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM : Study Empiris Pada PT Indofood Sukses Makmur Tbk yang Terdaftar di Bursa Efek Indonesia (BEI) periode 2011 -2015 (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
The purpose of this study to determine the effect of Current Ratio (CR) and Net Profit Margin (NPM) variables on stock prices either partially or simultaneously. This study uses data analysis methods, multiple regression, coefficient of determination t test and F test. From the results of this study, obtained multiple regression analysis yields the equation Y=161,785 -118,120X₁+ 9.239X₂ which means if the ratio of Current Ratio (CR) and Net Profit Margin (NPM) equal to zero (0) units then the Share Price of Rp.161,785,-/ sheet. Each CR increment is 1 unit while the other variable (NPM) is considered to be fixed, it will be followed by a decrease of Share Price of Rp. 118,120,-/ sheet. At each NPM increase of 1 unit while the other variable (NPM) is considered fixed, it will be followed by the increase of StockPrice of Rp. 9,239,-/ sheet. From t test analysis, t value arithmetic for CR and NPM are 0,778 and-0,415, respectively. with t table equal to 4,303 where t count <t table while value of Sig each is 0,518 and 0,718 or sig>0,05, so it can beconcluded that there is no significant influence between Current Ratio (CR) and Net Profit Margin (NPM) against stock prices. Based on the results of the calculation of the f test results obtained Sig> 0.05 or 0.680> 0.05. It can be concluded that simultaneously there is no positive and significant influence between Current Ratio (CR) and Net Profit Margin (NPM) to stock price. Based on the calculation of the coefficient of determination obtained results-0.359 that there is no effect of CR and NPM on stock prices. Stock prices can be influenced by other factors not examined by the author